2021
DOI: 10.3390/buildings11060246
|View full text |Cite
|
Sign up to set email alerts
|

BIM-Based Energy Analysis and Sustainability Assessment—Application to Portuguese Buildings

Abstract: Buildings are responsible for several negative impacts on the environment, most of them related to nonrenewable energy consumption, increasing the concern regarding buildings energy efficiency. In this context, computer software has been used to estimate the energy needs of the built environment, and the Building Information Modelling (BIM) methodology can be used to simplify this process. This study aims to validate a BIM-based framework to streamline the energy analysis of Portuguese buildings, based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 69 publications
(112 reference statements)
1
24
1
2
Order By: Relevance
“…Designers can quickly compare the life cycle impacts and costs of different building elements/envelopes. Additionally, the results of this method are also in line with the sustainability assessment method SBToolPT-H, allowing for the assessment of 3 out of 25 criteria [27,38].…”
Section: Discussionmentioning
confidence: 65%
“…Designers can quickly compare the life cycle impacts and costs of different building elements/envelopes. Additionally, the results of this method are also in line with the sustainability assessment method SBToolPT-H, allowing for the assessment of 3 out of 25 criteria [27,38].…”
Section: Discussionmentioning
confidence: 65%
“…Recently, there has been increasing research interest in BIM integration into sustainable assessment, and several research efforts have been initiated. BIM is most commonly used to support LEED [20]. For instance, Azhar et al [17] demonstrated a conceptual framework showing the relationship between BIM and LEED.…”
Section: Bim and Building Sustainability Assessmentmentioning
confidence: 99%
“…With most previous research efforts to apply BIM for sustainability assessment, a general conclusion is that BIM is still not oriented and has not gained its full potential for sustainable building design [20]. In addition, each method's assessment factors and indicators vary depending on local climate and environmental conditions, cultural and socio-economic aspects, standard practices, and regional diversifications.…”
Section: Bim and Building Sustainability Assessmentmentioning
confidence: 99%
“…The extent to which BIM-based energy assessments are possible greatly depends upon the BIM maturity stage [23,34] the project team operates at. The benefits offered by BIM and integration with sustainability assessments increase with each stage [5,26]. As can be seen from Table 5, most of the energy credits involve multiple stakeholders, and therefore, real-time information exchange between these disciplinary models is required for the automation of assessments for these credits.…”
Section: Energy Performance Evaluation With Bim-starting Pointsmentioning
confidence: 99%
“…By enabling performance evaluation in concurrence with the design process, it empowers design teams to make sustainable choices in the early stages of the project; • By replacing the traditional, manual methods of evaluation with an automated approach, it makes the process of verifying compliance with regulations or green certification requirements more efficiently; • By proper data management and linking information sources, it facilitates and streamlines the massive document management required for achieving these certifications [12,26,27].…”
mentioning
confidence: 99%